European boardrooms and the American Law Institute proposals - Norburn, David (Cranfield School of Management, 1985)
In May 1982, the highly prestigious American Law Institute (A.L.I.) proposed new rules to regulate the governance of large corporations. Although the furore of opposition from the world of business has still delayed the vote to accept these proposals, the interest aroused in both political and commercial arenas in an international context has been considerable. Not only would the proposals change contemporary strategic decision-making for most U.S. multi¬national corporations, but, if replicated in other countries would revolutionize the Boardroom. This paper analyses the implications of the A.L.I. proposals if implemented in a European environment. It argues that, if left to the business world, the proposals would be rejected on the criterion that companies would reduce their commitment to any risky project, particularly international ventures. In the academic sense, companies would sub-optimize their profile of strategic risk. Corporate economic performance would deteriorate in the medium-term. Conversely, since corporate law is made statute by politicians, not directors, the attraction of appearing to be societally empathetic makes it likely that many of the A.L.I. proposals will be the subject of international debate. Subject to this, it is vital for international corporations to put their own house in order, rather than encourage further political intervention. The paper concludes by proposing means to effect this proactive transition.